iPSC-based approach for human hair follicle regeneration - Vatanashevanopakorn, Chinnavuth; Sartyoungkul, Thanutchaporn (Frontiers in Cell and Developmental Biology, 2023)
Hair follicles are a multifunctional structure involved in physical protection, thermoregulation, sensational detection and wound healing. Formation and cycling of hair follicles requires dynamic interaction between different cell types of the follicles. Although the processes have been well studied, generation of human functional hair follicles with normal cycling pattern for clinical utilization has yet to be achieved. Recently, human pluripotent stem cells serve as an unlimited cell source for generating various types of cells including cells of the hair follicles. In this review, hair follicle morphogenesis and cycling, different cell sources used for hair follicle regeneration and potential strategies for hair follicle bioengineering using iPSCs are depicted. Challenges and perspectives toward the therapeutic use of bioengineered hair follicles for hair loss disorder are also discussed.